Hemolytic Uremic Syndrome: An Increasingly Recognized Public Health Problem. Issue 11 (2nd July 2018) - Murakami, Takuya; Akimoto, Tetsu; Yamazaki, Tomoyuki; Yoshizawa, Hiromichi; Okada, Mari; Miki, Atsushi; Nakagawa, Saki; Ohara, Ken; Sugase, Taro; Masuda, Takahiro; Kobayashi, Takahisa; Saito, Osamu; et al.
A 28-year-old man was referred and admitted to our hospital due to Escherichia coli O157–mediated hemorrhagic colitis with severe thrombocytopenia. A systemic workup concluded that the patient had acute pancreatitis as well as hemolytic uremic syndrome. The patient was ultimately discharged, with his platelet count having recovered. Our case serves an illustrative example of potentially serious complications of an increasingly recognized public health problem. Systemic studies on this topic are insufficient, and we strongly recommend the further accumulation of more experiences like ours. Several diagnostic and management concerns that emerged in this case are also discussed.